From Advocacy to Coercion: Public Opinion and Propaganda in the United States from the 1880s to the 1930s - Mathey, Éva (Hungarian Journal of English and American Studies, 2021)
Book review: Auerbach, Jonathan. Weapons of Democracy: Propaganda, Progressivism, and American Public Opinion. Baltimore: Johns Hopkins UP, 2015. xii + 220 pages. ISBN 978-1-4214-1736-3. Hb. 49.95.